2008
DOI: 10.1073/pnas.0712162105
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 mediates cancer protection but not prolongevity induced by caloric restriction

Abstract: Caloric restriction (CR) is the most potent intervention known to both protect against carcinogenesis and extend lifespan in laboratory animals. A variety of anticarcinogens and CR mimetics induce and activate the NF-E2-related factor 2 (Nrf2) pathway. Nrf2, in turn, induces a number of antioxidative and carcinogendetoxifying enzymes. Thus, Nrf2 offers a promising target for anticarcinogenesis and antiaging interventions. We used Nrf2-disrupted (KO) mice to examine its role on the biological effects of CR. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(164 citation statements)
references
References 42 publications
7
156
0
1
Order By: Relevance
“…CR was not effective against chemically induced tumorigenesis in the NFE2L2 knockout (KO) mice. AL NFE2L2 KO and CR NFE2L2 KO mice reached total tumor incidence at the age of 30 weeks, while 40% CR wt mice did not show any papillomas until 42 weeks of treatment (73). These data suggest that the anticarcinogenic effect of CR solely depends on the activity of NFE2L2 due to the lack of activation of the antioxidant defenses.…”
Section: Martin-montalvo and De Cabomentioning
confidence: 56%
“…CR was not effective against chemically induced tumorigenesis in the NFE2L2 knockout (KO) mice. AL NFE2L2 KO and CR NFE2L2 KO mice reached total tumor incidence at the age of 30 weeks, while 40% CR wt mice did not show any papillomas until 42 weeks of treatment (73). These data suggest that the anticarcinogenic effect of CR solely depends on the activity of NFE2L2 due to the lack of activation of the antioxidant defenses.…”
Section: Martin-montalvo and De Cabomentioning
confidence: 56%
“…Pearson et al [13] found one of the possible pathways that led from caloric restriction to anti cancer activity: Nrf2.…”
Section: Addressing Tumor Heterogeneitymentioning
confidence: 99%
“…Also certain compounds like sulforaphane and resveratrol can mimic the translational modifications found under caloric restriction [13][14].…”
Section: Addressing Tumor Heterogeneitymentioning
confidence: 99%
“…Interestingly, caloric restriction mimetic agents and caloric restriction activate Nrf2, 57 along with the activity of enzymes of the plasma membrane redox system, 57 so that Nrf2 has been implicated in the cancer protection induced by caloric restriction. 58 Furthermore, one of the consequences of Nrf2 activation in caloric restriction is to restrain vascular aging by reinforcing the antioxidant defenses of endothelial cells. 59 A number of experimental studies show that 4HPR, resveratrol, curcumin, xanthohumol, the isothiocyanate PEITC and CDDO triterpenoids can produce a dose-dependent prooxidant state inside tumor cells.…”
Section: Caloric Restriction and Angiopreventionmentioning
confidence: 99%